Chronic oral LPS administration does not increase inflammation or induce metabolic dysregulation in mice fed a western-style diet - Harvei, Silje; Skogen, Vemund; Egelandsdal, Bjørg; Birkeland, Signe; Paulsen, Jan Erik; Carlsen, Harald (Frontiers in Nutrition, 2024)
Lipopolysaccharides (LPS) present in the intestine are suggested to enter the bloodstream after consumption of high-fat diets and cause systemic inflammation and metabolic dysregulation through a process named "metabolic endotoxemia". This study aimed to determine the role of orally administered LPS to mice in the early stage of chronic low-grade inflammation induced by diet. We supplemented the drinking water with E. coli derived LPS to mice fed either high-fat Western-style diet (WSD) or standard chow (SC) for 7 weeks (n= 16-17). Body weight was recorded weekly. Systemic inflammatory status was assessed by in vivo imaging of NF-κB activity at different time points, and glucose dysregulation was assessed by insulin sensitivity test and glucose tolerance test near the end of the study. Systemic LPS exposure was estimated indirectly via quantification of LPS-binding protein (LBP) and antibodies against LPS in plasma, and directly using an LPS-sensitive cell reporter assay. Our results demonstrate that weight development and glucose regulation are not affected by LPS. We observed a transient LPS dependent upregulation of NF-κB activity in the liver region in both diet groups, a response that disappeared within the first week of LPS administration and remained low during the rest of the study. However, WSD fed mice had overall a higher NF-B activity compared to SC fed mice at all time points independent of LPS administration. Our findings indicate that orally administered LPS has limited to no impact on systemic inflammation and metabolic dysregulation in mice fed a high-fat western diet and we question the capability of intestinally derived LPS to initiate systemic inflammation through a healthy and uncompromised intestine, even when exposed to a high-fat diet.